THE RELATIONSHIP BETWEEN INTENSITY OF OBLIGATORY PRAYER AND MENTAL HEALTH: A SURVEY OF STUDENTS AT AS-SYAFIIYAH ISLAMIC UNIVERSITY - Sabrina, Lulu Luthfiah; Hadi, Abdul; Prabowo, Soekardi Hadi (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
With the massive development of information technology today, mental health in higher education has become a problem that has attracted the attention of several countries, especially in Indonesia. Digital-based distance learning provides a more exploratory and accelerated impact compared to traditional learning, but in psychological aspects, it can have a different impact. This study aims to analyze the relationship between the intensity of obligatory prayers and mental health in students of As-Syafi'iyah Islamic University, Jakarta. Using a quantitative method with a survey approach, the research design is correlational. The sampling method used is a purposive sampling technique, with the criteria being active UIA students performing obligatory prayers at the Al Barkah Mosque. The subjects in the study were 68 from the active UIA student population. Data for both research variables were collected using a five-strata Likert scale questionnaire. The data analysis technique used Pearson product-moment correlation analysis to determine the relationship between two variables and was carried out with the help of open source software, R Version 4.5.1 for Windows. The data for both research variables and the linear relationship specifications were all met. The results of the analysis show that there is a positive relationship between the intensity of obligatory prayers and mental health in students at As-Syafi'iyah Islamic University Jakarta.